2021
DOI: 10.18632/aging.202747
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from microRNA-512-5p-transfected bone mesenchymal stem cells inhibit glioblastoma progression by targeting JAG1

Abstract: In this study, we demonstrate that bone mesenchymal stem cell (BMSC)-derived exosomes alter tumor phenotypes by delivering miR-512-5p. miR-512-5p was downregulated in glioblastoma tissues and cells, and Jagged 1 (JAG1) was the target gene of miR-512-5p. We clarified the expression patterns of miR-512-5p and JAG1 along with their interactions in glioblastoma. Additionally, we observed that BMSC-derived exosomes could contain and transport miR-512-5p to glioblastoma cells in vitro . BMSC-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Mice with orthotopic implantation of GSCs were intraperitoneally administered Exo-miR124 every 2 days, and 50% of animals were still alive at 110 days with complete regression from pathological analysis of surviving mice [ 172 ]. Following this work, many studies on GBM also adopted similar delivery strategies to validate the therapeutic potential of different miRNAs including miR-584 [ 173 ], miR-133b [ 174 ], miR-199a [ 175 ], miR-375 [ 176 ], miR-512-5p [ 177 ], and miR-29a-3p [ 178 ]. All studies chose to genetically engineer the MSCs, either through direct transfection with synthetic miRNAs [ 173 , 174 , 175 ] or using lentiviral transduction to stably and endogenously express the miRNAs [ 176 , 177 , 178 ], and then isolate the secreted EVs.…”
Section: Current Status Of Msc-ev Therapeutic Applications In the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice with orthotopic implantation of GSCs were intraperitoneally administered Exo-miR124 every 2 days, and 50% of animals were still alive at 110 days with complete regression from pathological analysis of surviving mice [ 172 ]. Following this work, many studies on GBM also adopted similar delivery strategies to validate the therapeutic potential of different miRNAs including miR-584 [ 173 ], miR-133b [ 174 ], miR-199a [ 175 ], miR-375 [ 176 ], miR-512-5p [ 177 ], and miR-29a-3p [ 178 ]. All studies chose to genetically engineer the MSCs, either through direct transfection with synthetic miRNAs [ 173 , 174 , 175 ] or using lentiviral transduction to stably and endogenously express the miRNAs [ 176 , 177 , 178 ], and then isolate the secreted EVs.…”
Section: Current Status Of Msc-ev Therapeutic Applications In the Brainmentioning
confidence: 99%
“…Following this work, many studies on GBM also adopted similar delivery strategies to validate the therapeutic potential of different miRNAs including miR-584 [ 173 ], miR-133b [ 174 ], miR-199a [ 175 ], miR-375 [ 176 ], miR-512-5p [ 177 ], and miR-29a-3p [ 178 ]. All studies chose to genetically engineer the MSCs, either through direct transfection with synthetic miRNAs [ 173 , 174 , 175 ] or using lentiviral transduction to stably and endogenously express the miRNAs [ 176 , 177 , 178 ], and then isolate the secreted EVs. Xenograft nude mice were the model of choice, with GBM cells inoculated into the brain via intracranial [ 177 , 178 ] or subcutaneous [ 173 , 174 , 175 , 176 ] injections ( Table 2 ).…”
Section: Current Status Of Msc-ev Therapeutic Applications In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their effect on tumor growth is controversial [ 17 ā€“ 19 ]. BMSCs promote the development of breast cancer and prostate cancer [ 17 ], yet inhibit the progression of glioblastoma and hepatocellular carcinoma [ 18 , 19 ]. Moreover, OS cells may originate from BMSCs, while BMSCs regulate OS metastasis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have revealed that the association between tumor cells and stem cells in the tumor microenvironment can play a key role in modulating the development of cancer [17,18]. In the tumor environment, BMSCs are often associated with tumor cells to regulate tumorigenesis and metastasis of cancers [19,20].…”
Section: Introductionmentioning
confidence: 99%